Quality of life in patients with Parkinson's disease after subthalamic stimulation: An observational cohort study for outcome prediction - Jiin-Ling Jiang; Shin-Yuan Chen; Sheng-Tzung Tsai (Tzu Chi Medical Journal)
Objective: The objective of this study was to investigate the changes in health-related quality of life (HRQoL) and motor and depressive symptoms in patients with Parkinson's disease (PD) from baseline to 12 months following subthalamic nucleus deep brain stimulation (STN-DBS). Materials and Methods: The study utilized a prospective observational cohort design. Thirty-three PD patients with a good levodopa response but drug-related morbidity were included. PD Questionnaire-39 (PDQ-39) scores, unified PD rating scale (UPDRS) scores, Hoehn and Yahr stages, Beck Depression Inventory-II scores, and levodopa equivalent daily doses (LEDD) were obtained at baseline and 1 year after surgery. Results: The enrolled patients showed a significant HRQoL improvement of 21.43% at 12 months after STN-DBS as assessed by the PDQ-39 total score. There was a 34.92% improvement in UPDRS scores after STN-DBS at 1 year follow-up. Subitem analysis revealed significant improvement in UPDRS part II, III, and IV scores. The LEDD was significantly reduced by up to 27.36% 12 months after surgery. The preoperative PDQ-39 total score and LEDD predicted postoperative HRQoL in PD following STN-DBS. Conclusions: The current study demonstrated that STN-DBS surgery significantly improved HRQoL and motor outcomes of patients with PD. The preoperative PDQ-39 score and LEDD were predictors of the efficacy of postoperative HRQoL following surgery.